In the antechamber to extermination: the fate of Polish and Jewish convicts and “Night and Fog Prisoners” in the penitentiary subcamp Blachownia Śląska (Blechhammer) in 1942–1945 - Barth, Susanne (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2023)
The paper examines for the first time the role played by a penitentiary subcamp, that was set up in Blachownia Śląska (Blechhammer) by the penitentiary in Strzelce Opolskie (Gross Strehlitz) in 1942, as part of the Nazis’ plans to “Germanize” the annexed Silesian territories and to eliminate “racial” and political opponents.
Keywords: regional studies; region; Silesia; Poland; Czech Republic; Germany; regional journal; historical journal